2017
DOI: 10.1016/j.molmet.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular in vivo imaging of pancreatic islet cell physiology/pathology

Abstract: BackgroundDiabetes mellitus has reached epidemic proportions and requires new strategies for treatment. Unfortunately, the efficacy of treatment regimens on maintaining/re-gaining functional beta cell mass can, at the present, only be determined indirectly. Direct monitoring of beta cell mass is complicated by the anatomy of the endocrine pancreas, which consists of thousands to a million of discrete micro-organs, i.e. islets of Langerhans, which are scattered throughout the pancreas.Scope of reviewHere, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…5). Transplantation of human islets to the anterior chamber of the eye allows direct observation of various variables of islet morphology and function [69,70]. Furthermore, the exposed location of the islets in the eye allows for manipulation by local treatment or, for that matter, light, and can illustrate, for example, the effects of parasympathetic innervation [23,54].…”
Section: How To Further Investigate Alpha Cell-beta Cell Interactionsmentioning
confidence: 99%
“…5). Transplantation of human islets to the anterior chamber of the eye allows direct observation of various variables of islet morphology and function [69,70]. Furthermore, the exposed location of the islets in the eye allows for manipulation by local treatment or, for that matter, light, and can illustrate, for example, the effects of parasympathetic innervation [23,54].…”
Section: How To Further Investigate Alpha Cell-beta Cell Interactionsmentioning
confidence: 99%
“…The pancreatic islet explant work by Hedhammar and colleagues showed that it is plausible to transplant insulin secreting islet-like clusters from mouse and human primary cells grown on a silk foam into the mouse eye. The transplanted clusters remained capable of releasing insulin ( 80 ) and were vascularised and innervated within the eye ( 81 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exocytotic events may also be studied using total internal reflection fluorescence (TIRF) microscopy to track individual insulin granule fusion in the beta cells of intact human islets [127,128]. Another approach that facilitates the longitudinal and non-invasive functional imaging of islet cells in an in vivo environment involves the transplantation of isolated human islets into the anterior chamber (AC) of the mouse eye followed by microscopic analysis [129]. This technique allows the engraftment and subsequent innervation and vascularization of islets, at least in rodent models.…”
Section: Functional Imaging Of Human Beta Cellsmentioning
confidence: 99%